If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1(-3x + 9) = (x + -7) + -4(9x + -9) Reorder the terms: 6x + -1(9 + -3x) = (x + -7) + -4(9x + -9) 6x + (9 * -1 + -3x * -1) = (x + -7) + -4(9x + -9) 6x + (-9 + 3x) = (x + -7) + -4(9x + -9) Reorder the terms: -9 + 6x + 3x = (x + -7) + -4(9x + -9) Combine like terms: 6x + 3x = 9x -9 + 9x = (x + -7) + -4(9x + -9) Reorder the terms: -9 + 9x = (-7 + x) + -4(9x + -9) Remove parenthesis around (-7 + x) -9 + 9x = -7 + x + -4(9x + -9) Reorder the terms: -9 + 9x = -7 + x + -4(-9 + 9x) -9 + 9x = -7 + x + (-9 * -4 + 9x * -4) -9 + 9x = -7 + x + (36 + -36x) Reorder the terms: -9 + 9x = -7 + 36 + x + -36x Combine like terms: -7 + 36 = 29 -9 + 9x = 29 + x + -36x Combine like terms: x + -36x = -35x -9 + 9x = 29 + -35x Solving -9 + 9x = 29 + -35x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35x' to each side of the equation. -9 + 9x + 35x = 29 + -35x + 35x Combine like terms: 9x + 35x = 44x -9 + 44x = 29 + -35x + 35x Combine like terms: -35x + 35x = 0 -9 + 44x = 29 + 0 -9 + 44x = 29 Add '9' to each side of the equation. -9 + 9 + 44x = 29 + 9 Combine like terms: -9 + 9 = 0 0 + 44x = 29 + 9 44x = 29 + 9 Combine like terms: 29 + 9 = 38 44x = 38 Divide each side by '44'. x = 0.8636363636 Simplifying x = 0.8636363636
| (4x-9)/(7x^2+9) | | 5[x]=45 | | 5n+1=5(n-1) | | 8(k+11)-6k=9 | | 3u+4=22 | | 16x^2+5x=0 | | 7x+21=2x+56 | | 20y^2-15y^3= | | 1/4(x-3)=1/3(x-2) | | f(x)=5-.2x | | c/8+230/8=200 | | 22/1 | | 5r^2-16r+12= | | -5y-9=4y+2 | | 3k+34=4(6+3k)+1 | | -6-(-2n)=3-6+5 | | 15-2x=-19 | | .11x-.03(40000-x)=760 | | 5d+11=8d-7 | | 3x-2y+5y-8x= | | -2(x-5)-3x=120 | | (57/2)x=26.8 | | -2.3-5x-4.1-3x=-7x+1.6 | | 2(3m-4)=8m-11 | | -2(-2)+4(4)=8 | | -3(2x+4-3-6x)-2=10x | | i+i+1+i+2=228 | | -5/2-1/4 | | .04(2-q)=0.2(q+7) | | 2xy=8+5y | | 4x+40=-24 | | -3=-32t-1 |